Myocardial Biomarkers for Prediction of Cardiovascular Disease - Sundström, Johan (IOS Press, 2009)
The identification of those persons in the population who have the highest risk of future cardiovascular events is important for targeting intensive preventive efforts. This can be reliably done using a handful of long since established risk factors. The unmet need for new molecular biomarkers for prediction of cardiovascular events in the general population is therefore low. In order for a new biomarker to be used clinically for risk prediction, a statistically significant association of levels of the biomarker to adverse outcome is not enough, but the biomarker should also be demonstrated to add discriminative capacity beyond established risk factors. In contrast to the limited value of new biomarkers for risk prediction, their usefulness for unraveling the pathophysiology of cardiovascular disease is large. The myocardium is the source of a vast number of interesting biomarkers, of which a few may be useful for risk prediction in the general population. Two of these, troponin-I and the N-terminal fragment of brain natriuretic peptide, have passed tests of added discriminatory value. Numerous other biomarkers produced by cardiomyocytes or non-cardiomyocytes in the myocardium are promising, and if they are not proven useful for risk prediction, they will unquestionably enhance our understanding of cardiovascular disease.